Anticancer Activity, Mechanism, and Delivery of Allyl Isothiocyanate - Ammar Tarar; Sarah Peng; Soha Cheema; Ching-An Peng (Bioengineering, 2022)
Allyl isothiocyanate (AITC) is a phytochemical that is abundantly present in cruciferous vegetables of the Brassicaceae family, such as cabbage, broccoli, mustard, wasabi, and cauliflower. The pungent taste of these vegetables is mainly due to the content of AITC present in these vegetables. AITC is stored stably in the plant as its precursor sinigrin (a type of glucosinolate), which is physically separated from myrosin cells containing myrosinase. Upon tissue disruption, myrosinase gets released and hydrolyzes the sinigrin to produce AITC and by-products. AITC is an organosulfur compound, both an irritant and toxic, but it carries pharmacological properties, including anticancer, antibacterial, antifungal, and anti-inflammatory activities. Despite the promising anticancer effectiveness of AITC, its clinical application still possesses challenges due to several factors, i.e., low aqueous solubility, instability, and low bioavailability. In this review, the anticancer activity of AITC against several cancer models is summarized from the literature. Although the mechanism of action is still not fully understood, several pathways have been identified; these are discussed in this review. Not much attention has been given to the delivery of AITC, which hinders its clinical application. However, the few studies that have demonstrated the use of nanotechnology to facilitate the delivery of AITC are addressed.